2009
DOI: 10.1371/journal.ppat.1000487
|View full text |Cite
|
Sign up to set email alerts
|

The Glyceraldehyde-3-Phosphate Dehydrogenase and the Small GTPase Rab 2 Are Crucial for Brucella Replication

Abstract: The intracellular pathogen Brucella abortus survives and replicates inside host cells within an endoplasmic reticulum (ER)-derived replicative organelle named the “Brucella-containing vacuole” (BCV). Here, we developed a subcellular fractionation method to isolate BCVs and characterize for the first time the protein composition of its replicative niche. After identification of BCV membrane proteins by 2 dimensional (2D) gel electrophoresis and mass spectrometry, we focused on two eukaryotic proteins: the glyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 42 publications
3
85
0
Order By: Relevance
“…In parallel with these studies, we show here that PGK enzyme, involved in the downstream pathway of glycolysis, is critical for intramacrophagic growth and bacterial virulence in vivo. Recently, Fugier et al (14) have shown that inhibition of host cell GAPDH and enolase, both involved in glycolysis, resulted in reduced intracellular replication of Brucella. It is possible that Brucella is also using the host cell glycolysis to its advantage, as a source of energy.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with these studies, we show here that PGK enzyme, involved in the downstream pathway of glycolysis, is critical for intramacrophagic growth and bacterial virulence in vivo. Recently, Fugier et al (14) have shown that inhibition of host cell GAPDH and enolase, both involved in glycolysis, resulted in reduced intracellular replication of Brucella. It is possible that Brucella is also using the host cell glycolysis to its advantage, as a source of energy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have begun to illuminate these roles. These include endocytosis and membrane fusion, 17 translational control, 18 nuclear tRNA transport, 19 signaling, 20 pathogen virulence, 21 and cell death. 22 It is not clear how GAPDH can be targeted for these specific functions in the cell, but is believed to involve posttranslational modification of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…This is not very surprising since previous data reported proliferation outside ER-derived compartments (Arenas et al, 2000;Bellaire et al, 2005 (ERGIC) or autophagosomes, as proposed previously (Pizarro-Cerdá et al, 1998). ERGIC would be an interesting candidate since it was already shown that (i) Rab2, a Rab GTPase associated with ERGIC, is recruited on the BCVs and that (ii) the GAPDH/COPI/Rab2/PKC i/l complex, involved in retrograde transport between the ER and Golgi apparatus, is required for bacterial proliferation (Fugier et al, 2009). Preliminary data indicate that although the wild-type strain mainly colocalizes with an ERGIC marker (ERGIC53) at 12 h post-infection, though markedly less at 20 h post-infection, the DcstA mutant is not more frequently associated with this marker (data not shown), suggesting that DcstA does not accumulate and proliferate in ERGIC.…”
Section: Discussionmentioning
confidence: 99%